Automatic Irrigation System Based On Sensor and PH Detection of Soil Using Image Processing - ranjan Das, Manas; ranjan Das, Satya; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
The population of India has reached beyond 1.3billion and the rate of population is increasing with each passing days, and if it continues to next 2530 years, there will be a severe problem regarding food production, so it is necessary to develop as well as improve the agricultural sector. The farmers are currently suffering from water scarcity. Main goal of this paper is to provide an automatic irrigation system that saves the time, money, and power of the farmers. The traditional techniques of farmland irrigation require manual intervention and efforts. Human intervention in the agricultural fields easily minimized with the application of automated irrigation technology. Moisture sensors installed in the field. Each time there is a change in soil water content these sensors sense the shift and gives the micro-controller an interrupt signal. The soil is considered as one of the most precious natural resources whose soil pH properties used to define degree of ‘acidity’ or ‘basicity’ that affects the availability of nutrients and ultimately the growth of plants. The mobile camera used to capture the images and the pH value of the soil is determined after analysing the captured image. The crops or plants proposed after the analysis of the captured image, which is grown in the agricultural field. Because of the soil, pH quality identification, the chances of the crops from being spoiled decreases to an optimum level.